2020
DOI: 10.1021/acs.jpcb.0c05762
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Function of Myosin II: Investigation into the Recovery Stroke and ATP Hydrolysis

Abstract: Myosin regulates muscle function through a complex cycle of conformational rearrangements coupled with the hydrolysis of adenosine triphosphate (ATP). The recovery stroke reorganizes the myosin active site to hydrolyze ATP and cross bridge with the thin filament to produce muscle contraction. Engineered mutations K84M and R704E in Dictyostelium myosin have been designed to specifically inhibit the recovery stroke and have been shown to indirectly affect the ATPase activity of myosin. We investigated these muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…Baldo et al reported that acupuncture could regulate vasoactive substances and activate nitric oxide synthase III, and it also inhibits the angiotensin system and platelet adhesion. Inflammatory response after cerebral ischemia is mainly mediated by microglia, astrocytes, and leukocytes, including cytokines (IL-1, IL-6, IL-10, and TNF- α ) [ 22 ]. This inflammatory response induces the activation of gene expression and transcription factors that regulate the ischemic cascade and further aggravates the local inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Baldo et al reported that acupuncture could regulate vasoactive substances and activate nitric oxide synthase III, and it also inhibits the angiotensin system and platelet adhesion. Inflammatory response after cerebral ischemia is mainly mediated by microglia, astrocytes, and leukocytes, including cytokines (IL-1, IL-6, IL-10, and TNF- α ) [ 22 ]. This inflammatory response induces the activation of gene expression and transcription factors that regulate the ischemic cascade and further aggravates the local inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, understanding the pathogenic effects on interactions of the CTF with other proteins in the sarcomere (e.g. the thick filament) is under intensive study (49,50). Moreover, we hope to be able to expand this analysis to other regions of the CTF, such as the C-terminus of cTnT, and to extend the length of simulations in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These distributions and changes are difficult for an individual to assess, but a more automated process, such as deep machine learning, is exactly tailored to such a task and is a topic of ongoing research. In addition, understanding the pathogenic effects on interactions of the CTF with other proteins in the sarcomere (e.g., the thick filament) is under intensive study ( 49 , 50 ). Moreover, we hope to be able to expand this analysis to other regions of the CTF, such as the C-terminus of cTnT, and to extend the length of simulations in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The pioneering QM/MM , method can be used to focus attention on a smaller, predefined, region using quantum mechanics, while treating the rest of the system classically. This technique requires careful consideration of boundary and embedding effects, including interactions between the QM and MM regions, but is a valuable tool for studying free energies, catalysis including ATP hydrolysis, and photochemistry , integrates the quantum mechanical evaluation of the forces on each atomtypically done using DFTwith the classical dynamical evolution of the system itself.…”
Section: Introductionmentioning
confidence: 99%